Educação como instrumento de condução à evangelização e à civilidade: os missionários Loren e Alice Reno à frente do processo de criação do Colégio Americano Batista na cidade de Vitória/ES entre os anos de 1904 a 1935 - Assis, Elezeare Lima de (2019)
The research combines two objects of investigation: i. Strategies used by the American missionary couple, Loren and Alice Reno, for the formation, strengthening and legitimacy of the Baptist community in the State of Espírito Santo between the years of 1904 and 1935; ii. Idealizations and actions used in order to materialize the existence of the Baptist American School (Colégio Americano Batista) in the city of Vitória, during the Republic early years, and their contributions for the education history in Espírito Santo. The work is justified by the possibility of contribution, among the academic universe, proposing, from a historical approach, to forecast the educational approaches held in Brazil by non-Catholic religious groups, as well as the achievement of such approaches in the school culture. The research relevance consists on providing contributions, under the bias of history, to the field of analysis, usually prioritized in the educational filed. The work is included in the documental analysis perspective. It is guided by theoretical-methodological assumptions provided by micro history. It transited between the French and the Italian approach, taking into consideration that they both dialogue. It used Jacques Revele Carlos Ginzburg as main reference. The documental corpus is constituted of primary and secondary sources in the two first chapters. For the three last ones, the sources were basically primary. The research has answered the two investigation questions and has achieved the expected goals. It enabled the conclusion that the American missionaries’ actions and their interaction with the city resulted in the formation of two significant history institutions: a religious community with all precepts and culture, and a School that even nowadays, renders educational services to the city. The research detected the difficulty to find specific documents belonging to the school. The few existent documents were found dispersed all around private libraries of some Baptist community members. Besides, photographic records belonging to few former students in the beginning of the twentieth century or to their children and grandchildren that tend to disappear.